An assessment model to evaluate the level of collaborative manufacturing practices for tool and die development in Malaysia / Suman Selvarajoo - Suman , Selvarajoo (2024)
Industrial Revolution 4.0 (IR 4.0) has been getting much interest in many countries including Malaysia. As IR 4.0 looks at the vertical and horizontal integration, some of the key elements are the capacity and capability towards collaborative manufacturing across the manufacturing setup. Understanding the current practices in Malaysia, is important towards strategizing IR 4.0 integration within the Malaysian industries relying on tool and die, which is the focus of this study. The initial step of the research was site observation of manufacturing plants and tool and die fabricators. Followed by host company observation and then for a broader view, an industry survey was conducted involving industry practitioners in the local tool and die industry on the areas that contribute towards tool and die development and the issues surrounding it. This paved the way to understand the condition of the Malaysian industry through the samples which showed poor implementation of collaborative manufacturing. From those findings, a maturity assessment model was developed to evaluate the present state of the collaborative manufacturing of tool and die development of an organisation. The outcome from the literature review, site observation, host company observation, industry survey and C expert feedback provided the basis for the formation of the model which was then defined as Maturity Assessment of Collaborative Manufacturing of Tool and Die Development (MACM - T&D) based on 6 dimensions namely quality collaboration, design collaboration, technology, internal collaboration, management and external collaboration. The model was validated through case studies and anticipated to assist organisations to align their operation towards collaborative manufacturing while modernising their operation to escalate collaborative practices and progress towards IR 4.0. The model recorded positive feedback from the users who agreed with the model outcome and believed it would assist in their future orientation.